From Jirga to Civil Court: Navigating Land Justice in Post-FATA Khyber District (Journal of Social Sciences Review, 2025)
Justice forms the cornerstone of any society, and the entire judicial framework of modern systems is built upon this principle. However, the repercussions of inefficient or delayed justice disposal are severe and include heightened frustration, diminished confidence in the legal process, and the substantial costs associated with litigation. A significant backlog of court cases exists in Pakistan, resulting in prolonged and costly litigation processes. This backlog contributes to delays, making the judicial system less efficient and economical. Judicial setup has recently extended to the erstwhile FATA, replacing the old Frontier Crimes Regulations Act of 1900, which primarily relied upon the Jirga System to resolve criminal and civil disputes. This research attempts to find gaps/loopholes/shortcomings in the new judicial setup in deciding land-related civil disputes in tehsil Landikotal of district Khyber. The study has been able to highlight the prevalence of undocumented land disputes and their serious impact on people, communities and the law as a whole, explains a number of factors that lead to such disputes; these may include unclear property rights, historical disputes, poor land management, and lack of proper documentation. This study reveals legal and social consequences of land disputes, such as trade barriers, social unrest, loss of livelihood, and challenges to access justice. Need to resolve these conflicts through law, regulation and social intervention to prevent block increases and promote stability and equality in land title.
Keywords: Jirga System; Legal Framework; Undocumented Land Disputes Property Rights; Judicial Delays; FATA; Access to Justice